Gene Based Therapeutics and Targeted Nano Enabled Delivery Platforms for Management of Rheumatoid Arthritis - Babji Naik B; Usha Y Nayak; E Bhargav; Shaik Mahammad Shaheed (Journal of Pharmaceutical Innovation, 2026)

Buffalo Colostrum Peptides as Natural Antimicrobials Targeting Menaquinone by Inducing Oxidative stress Pathways in Mycobacterium smegmatis - B. E. Usha; H. S. Aparna (International Journal of Peptide Research and Therapeutics, 2026)

Microfilaruria of morphologically identified Dirofilaria repens and Brugia spp. in one cat and two dogs: Case series - Keerthana Santhosh; P. Preena; Sherin B. Sarangom; Y Ajith; Nongthombam Boby; Usha Narayana Pillai; S Ajithkumar; PV Tresamol (Topics in Companion Animal Medicine, 2026)

Role of agrobiodiversity in indigenous homegarden agroforestry systems of the eastern himalayas in enhancing food security - Rashmita Sharma; Usha Mina; Ashalata Devi; Rajbeer Singh; B. Mohan Kumar (Agroforestry Systems, 2026)

Glaucarubinone from Simarouba glauca DC. as a potential biocontrol agent for mosquito vector management - Sanju Singh; Abhishek Govekar; Debattam Mazumdar; Asmita Dhimmar; Harshal Sahastrabudhe; Apexa Gajjar; Pankaj Kumar; Srinu Tothadi; Prakash J. Dodiya; Usha P. Shinde; Ajeet Kumar Mohanty; Pramod B. Shinde; et al. (Natural Product Research, 2025)

Assessment of selected organic pollutants in sediments from a highly urbanized environment along the southeast coast of India - Muthukumar Chandrasekaran; Karthikeyan Panneerselvam; Kine Baek; Sissel B. Ranneklev; Merete Grung; Anders Ruus; Marianne Olsen; Vipin Babu. P; Ramu Karri; Tune Usha; M.V. Ramanamurthy (Marine Pollution Bulletin, 2025)

FPGA Processing for m-Delta (ẟ) Decomposition of L1 SLC Images for a Potential Smart Small Satellite Based CP-SAR Mission for Earth Observations - D. V. N. S. N. Murthy; J. K. Kishore; K. Mruthyunjaya Reddy; Stutee Gupta; L. J. Vijayakumar; N. Aparna; H. S. V. Usha Sundari Ryali; P. V. Jayasri; B. K. S. V. L. Varaprasad (Journal of the Indian Society of Remote Sensing, 2025)

Biophysical and Biochemical mechanism of plant resistance in Chilli against broad mite, Polyphagotarsonemus latus (Banks) - B. Keerthana; E. Sumathi; M. Murugan; H. Usha Nandhini Devi; M. Duvaraga Devi; A. Senthil (International Journal of Tropical Insect Science, 2025)

Identification of potential Akt activators: a ligand and structure-based computational approach - Harish B. Kumar; Suman Manandhar; Ekta Rathi; Shama Prasada Kabekkodu; Chetan Hasmukh Mehta; Usha Yogendra Nayak; Suvarna G. Kini; K. Sreedhara Ranganath Pai (Molecular Diversity, 2024)
The Akt pathway plays a significant role in various diseases like Alzheimer’s, Parkinson’s, and Diabetes. Akt is the central protein whose phosphorylation controls many downstream pathways. Binding of small molecules to the PH domain of Akt facilitates its phosphorylation in the cytoplasm and upregulates the Akt pathway. In the current study, to identify Akt activators, ligand-based approaches like 2D QSAR, shape, and pharmacophore-based screening were used, followed by structure-based approaches such as docking, MM-GBSA, ADME prediction, and MD simulation. The top twenty-five molecules from the Asinex gold platinum database found to be active in most 2D QSAR models were used for shape and pharmacophore-based screening. Later docking was performed using the PH domain of Akt1 (PDB: 1UNQ), and 197105, 261126, 253878, 256085, and 123435 were selected based on docking score and interaction with key residues, which were druggable and formed a stable protein–ligand complex. MD simulations of 261126 and 123435 showed better stability and interactions with key residues. To further investigate the SAR of 261126 and 123435, derivatives were downloaded from PubChem, and structure-based approaches were employed. MD simulation of derivatives 12289533, 12785801, 83824832, 102479045, and 6972939 was performed, in which 83824832 and 12289533 showed interaction with key residues for a longer duration of time, proving that they may act as Akt activators.

Pipecolic acid confers defence tolerance against Ralstonia solanacearum, the causal agent of bacterial wilt, by altering defence enzymes in tomato - Usha Sabharwal; Piyush Kant Rai; Piyush Tiwari; Kamlesh Choure; Saurabh kumar Mehta; R. B. Subramanian (Vegetos, 2024)

Identification of phytochemical as a dual inhibitor of PI3K and mTOR: a structure-based computational approach - B. Harish Kumar; Suman Manandhar; Sneha Sunil Choudhary; Keerthi Priya; Tanvi V. Gujaran; Chetan Hasmukh Mehta; Usha Yogendra Nayak; K. Sreedhara Ranganath Pai (Molecular Diversity, 2023)
Breast cancer is a common form of cancer that affects both men and women. One of the most common types of genomic flaws in cancer is the aberrations in the PI3K/AKT/mTOR pathway. The benefit of dual targeting PI3K as well as mTOR is that the kinase-positive feedback loops are more effectively inhibited. Therefore, in the current study, structure-based models like molecular docking, MM-GBSA, Qikprop, induced fit docking, simulated molecular dynamics (MD), and thermal MM-GBSA were used to identify the phytochemicals from the zinc 15 database, which may inhibit PI3K and mTOR. After docking the phytochemicals with PI3K (PDB 4FA6), ten ligands based on the docking score were selected, among which salvianolic acid C had the highest docking score. Hence, salvianolic acid A was also docked. All the ligands taken showed a binding energy of greater than − 30 kcal/mol. The predicted ADME showed that the ligands have druggable properties. By performing MD of the top five ligands and salvianolic acid A, it was found that ZINC000059728582, ZINC000257545754, ZINC000253532301, and salvianolic acid A form a stable complex with PI3K protein, among which ZINC000014690026 showed interaction with Val 882 for more than 89% of the time. Salvianolic acid A is already proven to suppress tumor growth in acute myeloid leukemia by inhibiting PI3K/AKT pathway, but the exact protein target is unknown. Therefore, the present study identifies new molecules and provides evidence for salvianolic acid A for dual inhibition. Further experiments must be performed both in vitro and in vivo to support the predictions of these computational tools. Graphical abstract

Transcription factors controlling the expression of oxidative stress associated genes in rice (Oryza sativa L.) - D. Sujitha; H. G. Jalendra Kumar; Garima Thapliayal; Garima Pal; P. A. Vanitha; Akshay Uttarkar; Mahesh Patil; B. H. Rajashekar Reddy; Vidya Niranjan; Usha Rayalcheruvu; Geetha Govind; M. Udayakumar; et al. (Plant Biotechnology Reports, 2023)

Molecular dynamics and structure-based virtual screening and identification of natural compounds as Wnt signaling modulators: possible therapeutics for Alzheimer’s disease - Suman Manandhar; Runali Sankhe; Keerthi Priya; Gangadhar Hari; Harish Kumar B.; Chetan H. Mehta; Usha Y. Nayak; K. Sreedhara Ranganath Pai (Molecular Diversity, 2022)
Wnt signaling pathway is an evolutionarily conserved pathway responsible for neurogenesis, axon outgrowth, neuronal polarity, synapse formation, and maintenance. Downregulation of Wnt signaling has been found in patients with Alzheimer’s disease (AD). Several experimental approaches to activate Wnt signaling pathway have proven to be beneficial in alleviating AD, which is one of the new therapeutic approaches for AD. The current study focuses on the computational structure-based virtual screening followed by the identification of potential phytomolecules targeting different markers of Wnt signaling like WIF1, DKK1, LRP6, GSK-3β, and acetylcholine esterase. Initially, screening of 1924 compounds from the plant-based library of Zinc database was done for the selected five proteins using docking approach followed by MM-GBSA calculations. The top five hit molecules were identified for each protein. Based on docking score, and binding interactions, the top two hit molecules for each protein were selected as promising molecules for the molecular dynamic (MD) simulation study with the five proteins. Therefore, from this in silico based study, we report that Mangiferin could be a potential molecule targeting Wnt signaling pathway modulating the LRP6 activity, Baicalin for AChE activity, Chebulic acid for DKK1, ZINC103539689 for WIF1, and Morin for GSk-3β protein. However, further validation of the activity is warranted based on in vivo and in vitro experiments for better understanding and strong claim. This study provides an in silico approach for the identification of modulators of the Wnt signaling pathway as a new therapeutic approach for AD. Graphical Abstract

A hypotonic gel-forming eye drop provides enhanced intraocular delivery of a kinase inhibitor with melanin-binding properties for sustained protection of retinal ganglion cells - Yoo Chun Kim; Henry T. Hsueh; Matthew D. Shin; Cynthia A. Berlinicke; Hyounkoo Han; Nicole M. Anders; Avelina Hemingway; Kirby T. Leo; Renee Ti Chou; HyeYoung Kwon; Matthew B. Appell; Usha Rai; et al. (Drug Delivery and Translational Research, 2022)

Assessment of Low Intensity Solar Radiation Susceptibility in 20 Wheat Varieties under Field Conditions Grown in Indo-Gangetic Plains of India - Usha Mina; S.D. Singh; B. Singh; S. Tiwari; Deepak Singh; Pranav Kumar (Journal of Crop Science and Biotechnology, 2019)

Synthesis and biological evaluation of imidazo[1,2- $${{\varvec{b}}}$$ b ]pyridazines as inhibitors of TNF- $${\varvec{\upalpha }}$$ α production - Shivaji S. Pandit; Mahesh R. Kulkarni; Usha Ghosh; Yashwant B. Pandit; Nitin P. Lad (Molecular Diversity, 2018)

Identification and validation of genomic regions influencing kernel zinc and iron in maize - Vemuri Hindu; Natalia Palacios-Rojas; Raman Babu; Willy B. Suwarno; Zerka Rashid; Rayalcheruvu Usha; Gajanan R Saykhedkar; Sudha K. Nair (Theoretical and Applied Genetics, 2018)

Induced defense response in wheat plants against Bipolaris sorokiniana following application of Bacillus safensis and Ochrobactrum pseudogrignonense - Jayanwita Sarkar; Usha Chakraborty; B. N. Chakraborty (Indian Phytopathology, 2018)

Computational Identification of MicroRNAs and Their Targets from Finger Millet (Eleusine coracana) - S. Usha; M. N. Jyothi; B. Suchithra; Rekha Dixit; D. V. Rai; R. Nagesh babu (Interdisciplinary Sciences: Computational Life Sciences, 2017)

Genetic variability and population structure in a collection of inbred lines derived from a core germplasm of castor - S. Senthilvel; Mobeen Shaik; K. Anjani; Ranjan K. Shaw; Poornima Kumari; C. Sarada; B. Usha Kiran (Journal of Plant Biochemistry and Biotechnology, 2017)

Assessing the genetic architecture of epithelial ovarian cancer histological subtypes - Gabriel Cuellar-Partida; Yi Lu; Suzanne C. Dixon; Peter A. Fasching; Alexander Hein; Stefanie Burghaus; Matthias W. Beckmann; Diether Lambrechts; Els Van Nieuwenhuysen; Ignace Vergote; Adriaan Vanderstichele; Jennifer Anne Doherty; et al. (Human Genetics, 2016)

Evaluation of QTLs for Shoot Fly (Atherigona soccata) Resistance Component Traits of Seedling Leaf Blade Glossiness and Trichome Density on Sorghum (Sorghum bicolor) Chromosome SBI-10L - K. N. S. Usha Kiranmayee; P. B. Kavi Kishor; C. Tom Hash; Santosh P. Deshpande (Tropical Plant Biology, 2016)

Diverse expression of sucrose transporter gene family in Zea mays - B. USHA; D. BORDOLOI; AJAY PARIDA (Journal of Genetics, 2015)

β-Adrenoreceptor Agonist Isoproterenol Alters Oxidative Status, Inflammatory Signaling, Injury Markers and Apoptotic Cell Death in Myocardium of Rats - Santosh K. Shukla; Suman B. Sharma; Usha R. singh (Indian Journal of Clinical Biochemistry, 2015)

Optimization of Chronomodulated Delivery System Coated with a Blend of Ethyl Cellulose and Eudragit L100 by Central Composite Design: In Vitro and In Vivo Evaluation - Om Prakash Ranjan; Usha Y. Nayak; M. Sreenivasa Reddy; Swapnil J. Dengale; Prashant B. Musmade; Nayanabhirama Udupa (Journal of Pharmaceutical Innovation, 2014)

Genome-wide association study of subtype-specific epithelial ovarian cancer risk alleles using pooled DNA - Madalene A. Earp; Linda E. Kelemen; Anthony M. Magliocco; Kenneth D. Swenerton; Georgia Chenevix-Trench; Yi Lu; Alexander Hein; Arif B. Ekici; Matthias W. Beckmann; Peter A. Fasching; Diether Lambrechts; Evelyn Despierre; et al. (Human Genetics, 2014)

Efficient genetic transformation of okra (Abelmoschus esculentus (L.) Moench) and generation of insect-resistant transgenic plants expressing the cry1Ac gene - M. Narendran; Satish G. Deole; Satish Harkude; Dattatray Shirale; Asaram Nanote; Pankaj Bihani; Srinivas Parimi; Bharat R. Char; Usha B. Zehr (Plant Cell Reports, 2013)

Cigarette smoking and risk of ovarian cancer: a pooled analysis of 21 case–control studies - Mette T. Faber; Susanne K. Kjær; Christian Dehlendorff; Jenny Chang-Claude; Klaus K. Andersen; Estrid Høgdall; Penelope M. Webb; Susan J. Jordan; Mary Anne Rossing; Jennifer A. Doherty; Galina Lurie; Pamela J. Thompson; et al. (Cancer Causes & Control, 2013)

Estimation of variables explaining urbanization concomitant with land-use change: a spatial approach - G. Sandhya Kiran; Usha B. Joshi (International Journal of Remote Sensing, 2013)

Hydrogeochemical processes controlling the high fluoride concentration in groundwater: a case study at the Boden block area, Orissa, India - R. K. Dey; S. K. Swain; Sulagna Mishra; Prachi Sharma; Tanushree Patnaik; V. K. Singh; B. N. Dehury; Usha Jha; R. K. Patel (Environmental Monitoring and Assessment, 2012)

Biological and molecular characterization of Capsicum chlorosis virus infecting chilli and tomato in India - S. R. Kunkalikar; P. Sudarsana; P. Rajagopalan; Usha B. Zehr; K. S. Ravi (Archives of Virology, 2010)

Impact of bottom trawling on sediment characteristics—a study along inshore waters off Veraval coast, India - Usha Bhagirathan; B. Meenakumari; K. V. Jayalakshmy; S. K. Panda; V. R. Madhu; D. T. Vaghela (Environmental Monitoring and Assessment, 2010)

Antifungal activity of Datura stramonium, Calotropis gigantea and Azadirachta indica against Fusarium mangiferae and floral malformation in mango - K. Usha; B. Singh; P. Praseetha; N. Deepa; D. K. Agarwal; R. Agarwal; A. Nagaraja (European Journal of Plant Pathology, 2009)

Studies on antioxidant status in Mugil cephalus in response to heavy metal pollution at Ennore estuary - E. Padmini; M. Usha Rani; B. Vijaya Geetha (Environmental Monitoring and Assessment, 2009)

Heavy metal and abiotic stress inducible metallothionein isoforms from Prosopis juliflora (SW) D.C. show differences in binding to heavy metals in vitro - B. Usha; Gayatri Venkataraman; Ajay Parida (Molecular Genetics and Genomics, 2009)

Genetic and molecular characterization of Candystripe1 transposition events in sorghum - Carlos H. S. Carvalho; Jayanand Boddu; Usha B. Zehr; John D. Axtell; Jeffery F. Pedersen; Surinder Chopra (Genetica, 2005)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Growth and Pigment Production by Hairy Root Cultures of Beta Vulgaris L. in a Bubble Column Reactor - Usha Mukundan; Edgard B. Carvalho; Wayne R. Curtis (Biotechnology Letters, 1998)

Panel discussion on “National laboratory network for immuno-diagnostics of infectious diseases (Nalind)” held on September 6,1997. Brief report - Harinath; P. Usha Sarma; G. K. Khuller; Raman K. Roy; Ambika Banerjee; T. Malati; U. Satyanarayana; P. Das; R. B. Narayanan; D. N. Rao; P. Bansal (Indian Journal of Clinical Biochemistry, 1997)

Chemical contamination and associated liver diseases in two species of fish from San Francisco Bay and Bodega Bay - CARLA M. Stehr; MARK S. Myers; DOUGLAS G. BURROWS; MARGARET M. Krahn; JAMES P. Meador; BRUCE B. McCAIN; USHA Varanasi (Ecotoxicology, 1997)